DNA Methylation and RNA-Sequencing Analysis Show Epigenetic Function During Grain Filling in Foxtail Millet (Setaria italica L.) - Wang, Tao; Lu, Quanwei; Song, Hui; Hu, Nan; Wei, Yangyang; Li, Pengtao; Liu, Yuling; Zhao, Zilin; Liu, Jinrong; Zhang, Baohong; Peng, Renhai (Frontiers in Plant Science, 2021)
Grain filling is a crucial process for crop yield and quality. Some excellent work has helped us to gain insight into the molecular mechanism in grain filling, whether it is associated with epigenetic modifications remains relatively unclear in foxtail millet. Global DNA methylation and transcriptome analysis were conducted in foxtail millet spikelet during different stages to interpret the epigenetic effects of grain filling process. We employed the whole-genome bisulfite deep sequencing and advanced bioinformatics to sequence and identify all DNA methylation during foxtail millet grain filling; the DNA methylation-mediated gene expression profiles and their involved in gene network and biological pathway was systematically studied. CHH methylation accounted for the largest percentage and gradually increased during grain filling. Among all test stages, the mean methylation levels were lowest at T2, followed by T4, which mainly occurred in CHG. Distribution of differentially methylated regions was varied in the different genetic regions for three contexts. In addition, gene expression was negatively associated with DNA methylation in gene-body except CHH context. Evaluation of the interconnection of the DNA methylome and transcriptome identified some stage-specific DEGs associated with DMR at different stages compared to T1 developmental stage, indicating that the potential function of epigenetics on expression regulation of genes related to specific pathway at different stages of grain development. Our results show the DNA methylation dynamic change and crucial function of DNA methylation in gene expression regulation, revealing the potential function of epigenetics in grain development of foxtail millet.